THE EFFECTIVENESS OF FORMATIVE FEEDBACK IN DEVELOPING ARGUMENTATIVE WRITING AMONG UNIVERSITY STUDENTS - Mamadieva Vazira Murodjon qizi (The Conference Hub, 2025)
This study investigates the effectiveness of formative feedback in enhancing argumentative writing skills among university students. By integrating a mixed-methods approach, the research examines students’ perceptions of feedback and its impact on their writing process. Data were collected through surveys, writing samples, and interviews, focusing on students' ability to construct coherent arguments, utilize evidence effectively, and refine their writing based on feedback. Results indicate that formative feedback significantly improved students' argumentative writing, promoting deeper engagement with the writing process and fostering critical thinking skills. The findings underscore the importance of continuous feedback mechanisms within academic settings to enhance writing proficiency.
Keywords: formative feedback, argumentative writing, university students, writing skills, critical thinking, educational practices, mixed-methods approach.